If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5b + -1b + 15b + -10b + -12 = 4 Reorder the terms: -12 + -5b + -1b + 15b + -10b = 4 Combine like terms: -5b + -1b = -6b -12 + -6b + 15b + -10b = 4 Combine like terms: -6b + 15b = 9b -12 + 9b + -10b = 4 Combine like terms: 9b + -10b = -1b -12 + -1b = 4 Solving -12 + -1b = 4 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1b = 4 + 12 Combine like terms: -12 + 12 = 0 0 + -1b = 4 + 12 -1b = 4 + 12 Combine like terms: 4 + 12 = 16 -1b = 16 Divide each side by '-1'. b = -16 Simplifying b = -16
| y=4(5x+5)+12 | | 5-25b=10 | | -10p-16p+8p+15p+8=-7 | | 90-(3+9)*7= | | cos(65)=(7/x) | | 5x^2=900 | | .4x+3.91=21.05 | | 30+y+x=180 | | 16t-7t-8t-t+t+2=16 | | 12=n/9=1 | | 2x-14y=-22 | | 3(2t-6)=2(3r-9) | | 5x+5(4x+12)=10 | | 2(x-3)=1/2x | | 3(n+1)-2n=0 | | -2z+13z+13z-20z=-20 | | 0=4+2n | | 13+b=-4 | | 4/7y-8=2/7y-10 | | 2x-14y=22 | | 3(4x+5)-3y=-15 | | 8-2x=-13 | | 8(-2i)(-5-4i)= | | (8(-3)-1)-(-3)+3= | | 82(0.006889-x^2)=2x | | 3x-3y=4x+5 | | 19=4-2x | | 32x-4=3 | | -16a+11a+7a=-16 | | w/- | | 82(0.006888-x^2)=2x | | -16+y=5 |